Penerapan Metode Dijkstra Pada Sistem Informasi Pencarian Jarak Terpendek Menuju Rumah Sakit di Wilayah Jakarta Barat - Syarifudin, Imam; Yunita, Y; Ramanda, Kresna (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
The health center has a very important role because it can help care for and care for people who are sick and provide emergency room services (UGD). for immigrants in the West Jakarta area who still have not seen where the health center is and have to go through which route is closer to where they are. There are several algorithms that can be used to determine the shortest path, one of which is using the Dijkstra algorithm. Search for the shortest distance to the hospital in the West Jakarta area using the Dijkstra method. The problem of finding the shortest path on the graph is one of the optimization problems. The graph used in the search for the shortest path is a wighted graph, which is a graph where each side is given a value or weight. In determining the shortest path, Dijkstra's algorithm starts from the initial node to the destination node. Where each node has a predetermined distance value. The results of this study indicate that Dijkstra's Algorithm is the right method to produce the shortest route for finding the path to hospitals in the West Jakarta area.